Start-up acquisition: motivations, difficulties and lesson learned - Banlaky, Luis Felipe Marin (2016)
In a continuous survival effort, corporations search for different ways to expand their business within the market in which they already operate, or within new desired markets. To reach their objectives, the employees innovate through their initiatives, an act called corporate entrepreneurship. There are many ways that corporates can have an entrepreneurial behaviour, such as through the acquisition of another company. When acquiring a different company, a corporation has as its motivation the desire of some new attributes that either complement or will be part of their indicial objectives. After the acquisition, the integration process between the two (or more) partners is often complicated and painful. The aim of this study is to identify; what are the buying motivations, the problems encountered during the merging process of merge between the partners, and the lessons learned by big/medium corporations when acquiring a Start-up. There is a vast amount of literature concerning the acquisition by big corporations but, when talking about the acquisition of start-ups, one discovers an unexplored gap due to a lack of literature on this subject. The results of this study have been collected through in-depth interviews with employees and entrepreneurs that have taken part in the entire process of acquisition of SAMURAI by Momentum and of Save-me by Buscapé. The results are six suggestions of topics that should be taken into consideration by big/medium corporations when taking the decision of acquiring a start-up: (i) The client base of the acquired company should be previously considered; (ii) a closer contact between the management of both companies before the acquisition is crucial; (iii) hiring a consultancy company to advise during the merge process can be primordial; (iv) the entrepreneur has a central importance for the future of the merged firm; (v) the integration mode has to be carefully choice having the (iv) creation of a corporate venture as a great choice to be consider.